Hubungan Pengetahuan Dan Penerapan Sanitasi Ibu Rumah Tangga Terhadap Sanitasi Dapur di Kelurahan Pucanganom Sidoarjo (Lembaga Pengembangan Kinerja Dosen, 2025)
The study aims to (1) Determine the level of knowledge of housewives about kitchen sanitation in Pucanganom village. (2) Determine the conditions of sanitation implementation in housewives' kitchens in Pucanganom village. (3) Determine the relationship between knowledge of kitchen sanitation and the conditions of sanitation implementation in housewives' kitchens in Pucanganom village. The type of research carried out was field research with a quantitative descriptive method. The sampling technique used the Purposive Sampling method. The sample population in this study was 36 house samples in Pucanganom Village, Sidoarjo Regency in 2021. The data collection instrument used a questionnaire sheet (Knowledge Test). The data analysis technique used univariate and bivariate analysis. The results of the study in Pucanganom Village revealed that (1) the majority of housewives had a sufficient to high understanding of the conceptual aspects of kitchen sanitation; (2) the implementation of sanitation had not been fully implemented. For example, the use of sinks for washing hands, storing cooking utensils in closed containers, and separating food ingredients in the refrigerator are still rarely implemented; (3) Statistical tests using Chi-Square showed that there was no significant relationship between the level of knowledge and kitchen sanitation practices.